Hindu Survey of Indian agriculture 2002 (Chennai, 2002)
Indian wheat being loaded onto a Philippines bound vessel at the Vishakapattinam Port. Indian farmers will have to be more competitive and quality-oriented to find an established berth in the global market. Given the support of sound government policies, good infrastructural facilities, technological innovations and clean post-harvest management practices millions of small and marginal farmers will stand up to meet the demand of the international market. Production by the masses, the spirit of cooperation and zest for quality standards should be the hallmarks of Indian agriculture when it enters the global trade.
Keywords: Agriculture survey 2001